Critical appraisal of health claims: science teachers' perceptions and practices. Issue 5 (1st August 2016) - Nordheim, Lena; Pettersen, Kjell Sverre; Flottorp, Signe; Hjälmhult, Esther
Abstract : Purpose: Critical appraisal skills are necessary to navigate the numerous contradictory and pseudo-scientific claims in the popular media. Health and science education in schools is essential for promoting these skills in students. This study explores lower secondary school science teachers' perceptions and reported practices related to teaching critical appraisal of health claims. Design/methodology/approach: Interpretive description strategy guided the study process. A purposeful sample of 25 Norwegian teachers was interviewed individually or in groups. Interviews were analysed using the constant comparative method. Findings: One main theme, "unexploited opportunities for teaching critical appraisal", and three sub-themes were identified: "inattentive to the relevance of critical appraisal", "prioritise facts over critical appraisal", "limited competency in critical appraisal". Teachers' descriptions of science sessions devoted to health education uncovered important opportunities for teaching critical appraisal of health claims. However, teachers did not appear to seize opportunities because they seemed inattentive to the relevance of teaching critical appraisal, they reported to prioritise teaching health content knowledge, and teachers themselves revealed limited expertise in assessing health claims critically. Practical implications: The findings suggest that science teachers need support to take better advantage of the links between health and science education to enhance students' critical appraisal skills. Originality/value: This study adds depth to the understanding of issues and challenges faced by science teachers regarding critical appraisal of health claims, which is an important aspect of health education schools.